Changes in Payer Mix and Physician Reimbursement After the Affordable Care Act and Medicaid Expansion - Christine D. Jones MD, MS; Serena J. Scott MD, MBA; Debra L. Anoff MD; Read G. Pierce MD; Jeffrey J. Glasheen MD (SAGE Publishing, 2015)
Although uncompensated care for hospital-based care has fallen dramatically since the implementation of the Affordable Care Act and Medicaid expansion, the changes in hospital physician reimbursement are not known. We evaluated if payer mix and physician reimbursement by encounter changed between 2013 and 2014 in an academic hospitalist practice in a Medicaid expansion state. This was a retrospective cohort study of all general medicine inpatient admissions to an academic hospitalist group in 2013 and 2014. The proportion of encounters by payer and reimbursement/inpatient encounter were compared in 2013 versus 2014. A sensitivity analysis determined the relative contribution of different factors to the change in reimbursement/encounter. Among 37 540 and 40 397 general medicine inpatient encounters in 2013 and 2014, respectively, Medicaid encounters increased (17.3% to 30.0%, P < .001), uninsured encounters decreased (18.4% to 6.3%, P < 0.001), and private payer encounters also decreased (14.1% to 13.3%, P = .001). The median reimbursement/encounter increased 4.2% from $79.98/encounter in 2013 to $83.36/encounter in 2014 ( P < .001). In a sensitivity analysis, changes in length of stay, proportions in encounter type by payer, payer mix, and reimbursement for encounter type by payer accounted for −0.7%, 0.8%, 2.0%, and 2.3% of the reimbursement change, respectively. From 2013 to 2014, Medicaid encounters increased, and uninsured and private payer encounters decreased within our hospitalist practice. Reimbursement/encounter also increased, much of which could be attributed to a change in payer mix. Further analyses of physician reimbursement in Medicaid expansion and non-expansion states would further delineate reimbursement changes that are directly attributable to Medicaid expansion.